The effects of grapeseed extract and low level laser therapy administration on the liver in experimentally fractured mandible (Annals of Medical Research, 2021)
Aim: The present study investigated the changes in the liver tissues of rats with experimentally fractured mandible following the use of Grape Extract (GSE) and Low Level Laser Therapy (LLLT) in healing the fracture in dentistry.
Keywords: Low Level Laser Therapy; Mandibular Fracture Recovery; Oxidative Stress; Grapeseed Extract; Liver; Rat.